"Spasimi d'ira, spasimi d'amore". Le atmosfere nell'opera lirica (Lebenswelt. Aesthetics and philosophy of experience., 2017)
Nowadays, atmospheres  are a frequent topic in the philosophy of music. However, ‘music’ is frequently understood with a generical meaning. On the contrary, this paper aims to apply the theory of atmospheres in a defined musical genre: the Italian Opera. Opera is grounded on three expressive elements – music, libretto and stage. For this reason, it is reductive to talk only about the relationship between music and atmospheres. The studies about Opera has often treated separately its three expressive levels; the theory of atmospheres, as olistic approach, seems to offer a renewed integrity to the analysis of Opera – by rediscovering its performative character. In this perspective, the hic et nunc of a particular performance is an important element to analyze as the score as the libretto, by paying attention to the eventual conflict between the ‘potential atmospheres’ of the texts (score and libretto) and the ‘derivative atmospheres’ of the contemporary staging – especially of the ‘displaced’ and ‘radical’ ones.